The functional domain of adenylate cyclase associated with entry into meiosis in Saccharomyces cerevisiae. - Uno, I (1990)
Diploid yeast cells that carry a part of the CYR1 gene deficient in a region coding for the N-terminal domain of adenylate cyclase were growth arrested and accumulated unbudded cells after inoculation into complete medium or nitrogen-free medium, but produced many cells which had one or more buds after incubation in sporulation medium. The cells incubated in sporulation medium had abnormal spindles which were free from the spindle pole bodies, larger in size, or frequently distributed in cytoplasm. The levels of cyclic AMP in these cells did not decrease to the wild-type level after transfer to the sporulation medium and remained at a constant level. The results suggest that the N-terminal domain of adenylate cyclase is associated with the regulatory function for sporulation. The environmental signals for sporulation may be transferred to the adenylate cyclase system through a factor that negatively interacts with the N-terminal domain of this enzyme.